Safety, efficacy and immunogenicity of therapeutic vaccines in the treatment of patients with high-grade cervical intraepithelial neoplasia associated with human papillomavirus: a systematic review protocol - Luís Carlos Lopes-Júnior; Gabriela Pereira-da-Silva; Caroline Amélia Gonçalves; Fernando Kenji Nampo; Adriana Zilly; Paulo César Morales Mayer (BMJ Open)
Introduction Eighty per cent of the sexually active population will get human papillomavirus (HPV) infection, which is the most prevalent sexually transmitted disease worldwide. Persistence of high-grade HPV infection may evolve to a cervical intraepithelial neoplasia (CIN), and these lesions may be precursors of cervical cancer. However, this progression can be prevented by the administration of therapeutic vaccines which use the main oncoproteins responsible for cancer development in an attempt to trigger a more specific and effective immunological response against this disorder. We aim to evaluate the safety, efficacy and immunogenicity of therapeutic vaccines in the treatment of patients with high-grade CIN 2/3 associated with HPV.Methods and analysis A systematic review of clinical trials will be undertaken. Medline, Excerpta Medica Database, Cochrane Central Register of Controlled Trials, Web of Science, Latin American and Caribbean Health Sciences Literature, Scientific Electronic Library Online and Scopus will be searched, with no restriction regarding publication date. Primary outcomes will include measures related to safety, efficacy and the immunogenicity of the therapeutic vaccines used in these patients. Study selection will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Methodological appraisal of the studies will be assessed by the Cochrane Risk-of-Bias Tool for randomised controlled trials, and the quality evidence of the risk of bias in single studies will be evaluated by Grading of Recommendations Assessment, Development and Evaluation. A narrative synthesis will be done for all included studies. Outcomes will be analysed according to the subgroups of HPV type, CIN grade, route of vaccine administration and vaccine type. Also, if sufficient data are available, a meta-analysis will be conducted. The effect sizes will be generated using Hedges’ g score for both fixed and random effect models. I2 statistics will be used to assess heterogeneity and identify their potential sources.Ethics and dissemination Ethical approval is not required as primary data will not be collected. Findings will be disseminated widely via peer-reviewed publication and in different media, for example, conferences, congresses or symposia.PROSPERO registration number CRD42017077428.